Faktor-Faktor yang Mempengaruhi Pengelolaan Dana Bantuan Oprasional Sekolah (BOS) pada Satuan Pendidikan di Kabupaten Bengkalis - Em Fikri Alfiansyah; Ruhul Fitrios; H M Rasuli (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to examine and analyze the influence of the competence of human resources contained in the treasurer and school leadership as well as community participation on the management of BOS funds in the Education unit in Bengkalis Regency. The population in this study were all elementary / junior high schools in the scope of the Bengkalis Regency Education Office, while the sample amounted to 176 schools consisting of 126 elementary schools and 50 junior high schools. Respondents were taken by means of random sampling, in order to obtain a total of 528 respondents consisting of the principal, teacher/treasurer and the local community/school committee. Data analysis uses quantitative analysis methods that use numbers and statistical calculations. The data analysis tool in this study uses structural equation modeling-partial least square (SEM-PLS) using WarpPLS version 5.0 software. Based on the results of the analysis, it can be concluded that the competence of treasurer human resources, managerial competence of school principals and community participation affect the management of boss funds in the education unit in Bengkalis Regency.